Analysis of Foreign Culture Representation in the 10th Grade English Compulsory Textbook - Prayudha.S, Joko; Azwandi, Azwandi; Syafryadin, Syafryadin (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2024)
Culture is a way of life or outlook that applies in a particular region or community. Through culture, a person will gain an understanding of diverse intercultural matters. This research analyzed the foreign cultural representation in English compulsory textbooks for the 10th-grade students of the senior high school published by the Ministry of Education and Culture of the Republic of Indonesia as an introduction to culture to Indonesian students. This research used a mixed method by using a descriptive approach. The data was collected through analysis of the content in pictures, images, passages, charts, and everything in English textbooks that related to foreign culture representation. Next, data was analyzed by compiling based on the types of culture, dissembling the different types of culture, re-assembling culture based on the right type, interpreting, and concluding. The results showed that the foreign cultural representation on English compulsory textbook consists of four cultural aspects, they are aspect of product culture, aspect of practice culture, aspect of perspective culture, and aspect of person culture. Based on the research results, English teachers must provide a good understanding of foreign cultures to students so they can gain insight into intercultural competence.